Effects of Oral Gamma-Aminobutyric Acid (GABA) Administration on Stress and Sleep in Humans: A Systematic Review - Hepsomali, Piril; Groeger, John A.; Nishihira, Jun; Scholey, Andrew (Frontiers in Neuroscience, 2020)
Background: Gamma-aminobutyric acid (GABA) is a non-proteinogenic amino acid and is the main inhibitory neurotransmitter in the mammalian brain. GABA’s stress-reducing, and sleep enhancing effects have been established. However, although several human clinical trials have been conducted, results regarding the role of natural and/or biosynthetic oral GABA intake on stress and sleep are mixed. We performed a systematic review to examine whether natural and/or biosynthetic oral GABA intake has an effect on stress and sleep. Methods: We systematically searched on PubMed database for studies published up to February 2020 following PRISMA guidelines. Only placebo-controlled human trials that assessed stress, sleep and related psychophysiological outcomes as a response to natural GABA (i.e. GABA that is present naturally in foods) or biosynthetic GABA (i.e. GABA that is produced via fermentation) intake were included. Results: Fourteen studies met the criteria and were included in the systematic review. Overall, there is limited evidence for stress and very limited evidence for sleep benefits of oral GABA intake. Conclusion: Although more studies are needed before any inferences can be made about the efficacy of oral GABA consumption on stress and sleep, the current evidence suggests that natural and biosynthetic GABA intake may have advantageous effects on stress and sleep.